The Social Self : Hawthorne, Howells, William James, and Nineteenth-Century Psychology - Alkana, Joseph, 1953- (Book collections on Project MUSE., 1997)
American literary history of the nineteenth-century as a conflict between individualistic writers and a conformist society. In The Social Self, Joseph Alkana argues that such a dichotomy misrepresents the views of many authors. Sudden changes caused by the industrial revolution, urban development, increased immigration, and regional conflicts were threatening to fragment the community, and such writers as Nathaniel Hawthorne, William James, and William Dean Howells were deeply concerned about social cohesion. Alkana persuasively reintroduces Common Sense philosophy and Jamesian psychology as w.